Adaptable Design for the HSB Living Lab - flexible, co-created spaces in student housingg - Hagy, Shea; Balay, Paul (My University, 2014)
This thesis aims to provide a collection of materials for use as a resource to catalyse the creation and design of the HSB Living Lab. The HSB living lab is an on-going project for the creation of a ‘living laboratory’ that will take the form of student-housing and be built in the coming year on the Johanneberg campus of Chalmers University of Technology in Gothenburg, Sweden. The Information and materials included in this report were collected through stakeholder interviews and literature review. Throughout this work key elements of the HSB Living Lab project are presented and discussed including organisational structure, the concepts of innovation, co-creation and adaptability as well as the potential research and stakeholder prerequisites that may impact the building design. This thesis contributes to the general reflection around the HSB Living Lab by proposing both concrete design solutions and laying out a framework for design. The specific needs of the stakeholders have shaped the methodology and approach to design, resulting in adaptable design solutions for the HSB Living Lab infrastructure.
Keywords: Byggnadsteknik; Building Futures; Building engineering; Building Futures